International Transportation and Marketing of Canadian Potash - Kevin B. Doyle (Canadian Institute of Mining, Metallurgy and Petroleum, 1976)
"Canada now supplies 23 per cent of the world demand for potash. Although potash is produced by many countries, Russia and Canada have the greatest reserves and capability to supply the future substantial demand over the next decade. It is estimated that demand will grow from 38,000,000 mt KCl in 1975-76 to 60,000,000 mt KCl in 1985-86. Current firm expansion plans and development underway in the world will move Russia to the forefront in supplying this demand growth. Russia will move from supplying 40 per cent of world demand in 1975 to supplying as much as 52 per cent in 1981. Canadian deposits suffer from natural disadvantages, such as high costs and risks of mine development and operation, and high-cost transportation to international markets, but experience has shown that these natural barriers can be surmounted to effectively compete in these international markets. However, Canadian potash is losing out in the race to supply the growth in the world potash demand over the next ten years because of artificial barriers raised through the unhealthy environment created by the current battle between different levels of government and the industry over resource taxation and legislation."